2020
DOI: 10.1177/0020872820956261
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the territories of transition: An exploration of the experiences of transnational social workers in Aotearoa New Zealand

Abstract: This qualitative study conducted three focus groups with transnational social workers (TSWs) in three cities of Aotearoa New Zealand. The aim of the study was to examine the transitional experience of TSWs, particularly in relation to any strategies and mechanisms existing in the host country to facilitate their personal and professional transition. A significant finding is that a coherent profession-wide programme for facilitating the transition is absent as the existing practices are mostly within the employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Differences in approaches to practice, the lack of supportive supervision, restrictions to the social work role and lack of autonomy and the negative public perception of social work, contributed to social workers' experience of cultural dislocation (Fouche ´et al, 2014). International practitioners can enrich and enliven social work practice globally if host countries recognise the skills they bring (Bartley et al, 2012;Peter et al, 2020). Our participants expressed the feeling that whilst their labour is needed, their unique potential contribution through integrating models of practice used in South Africa is discouraged and they are expected to assimilate to local practices quickly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in approaches to practice, the lack of supportive supervision, restrictions to the social work role and lack of autonomy and the negative public perception of social work, contributed to social workers' experience of cultural dislocation (Fouche ´et al, 2014). International practitioners can enrich and enliven social work practice globally if host countries recognise the skills they bring (Bartley et al, 2012;Peter et al, 2020). Our participants expressed the feeling that whilst their labour is needed, their unique potential contribution through integrating models of practice used in South Africa is discouraged and they are expected to assimilate to local practices quickly.…”
Section: Discussionmentioning
confidence: 99%
“…. The lack of support in terms of orientation (Peter et al, 2020) leaves migrant social workers often feeling judged (Staniforth and Connor, 2021). Hunt (2007) and Lillis et al (2006) also reported that overseastrained health professionals experience both discrimination and a lack of equal recognition in the workplace.…”
Section: Experiencing Racism In the English Social Work Environmentmentioning
confidence: 99%
“…Without this structure and oversights, variations in what programs emphasize can create problems of alignment between social work education, and alignment with licensure examinations and expectations (Zeng et al, 2020). Additionally, as Peter et al (2020) opine, social work is unique because it is considered a global profession, enabling practitioners to move between countries to live and work. Where social work programs are not accredited or social workers are not licensed, could result in complicated and lengthy processes for obtaining licensing or registration outside of where one is qualified.…”
Section: The Uae Contextmentioning
confidence: 99%
“…As practitioners, managers, educators, professional bodies and the Social Workers Registration Board (SWRB), we all share in the reciprocal responsibility of ensuring that our manuhiri (visitors) have ample opportunity to seek out cultural encounters on the path to ethically ground their practice. (p. 166) Peter et al (2020) conducted focus groups with migrant social workers in Aotearoa New Zealand in 2017. They conceptualised the process of acculturation as moving between territories.…”
Section: Bicultural Contextmentioning
confidence: 99%